The macroeconomic impact of the Next Generation EU instrument on the euro area - Krzysztof Bankowski; Marien Ferdinandusse; Sebastian Hauptmeier; Pascal Jacquinot; Vilém Valenta (European Central Bank (ECB), 2021)
In response to the economic fallout from the coronavirus (COVID-19) pandemic, the European Council agreed on the Next Generation EU (NGEU) instrument. NGEU allows the European Commission to issue debt to finance grants and loans to EU Member States, with the disbursement of funds intended to be weighted towards the countries most affected by the crisis. This paper assesses the macroeconomic impact on the euro area of different uses of NGEU, using a large dynamic stochastic general equilibrium (DSGE) model of the euro area and global economy (EAGLE) that has been adapted to reflect the modalities of the NGEU instrument. Three uses of NGEU loans and grants are explored: (i) productive public investment, (ii) unproductive government spending, and (iii) replacing or repaying existing sovereign debt. The EAGLE results are cross-checked with a semi-structural model (ECB-BASE) and with the basic model elasticities (BMEs) of the forecasting models in use in the national central banks of the Eurosystem.
Keywords: C54; E62; E65; F54; F47; 330; EMU; euro area; COVID-19; NextGenerationEU; public investment